On the Integrative Interconnection of Extrajudicial and Judicial Resolution of Administrative-Tort Cases - N. V. Landerson (Сибирское юридическое обозрение, 2021)
The article considers some features of the integrative relationship between public administration and courts in two types of administrative-tort cases: 1) in cases of administrative offences (or otherwise - in cases of administrative-punishable torts, since the consideration and resolution of this category of administrative-tort cases essentially entails the appointment of administrative penalties according to the rules provided for by Code of the Russian Federation on Administrative Offences); 2) in cases of violations of mandatory requirements detected and suppressed by public administration bodies during control and supervisory proceedings (or otherwise - in cases of administrativeavoidable violations, since the consideration and resolution of this category is administrative-tort cases on the merits entail the application of such a measure of administrative enforcement and restorative influence as the introduction of an order to eliminate violations of mandatory requirements under the rules provided for by the legislation of the Russian Federation: 1) add Article 28.8 of the Code of the Russian Federation on Administrative Offences, providing that when drawing up a protocol on an administrative offense, the consideration of which is attributed to the competence of another body, a decision is made on the transfer of the case materials by authority (if the case is subject to consideration by a public administration body) or by jurisdiction (if the case is subject to consideration in a court of general jurisdiction); 2) as an alternative option for further improvement of the administrative-procedural legislation of the Russian Federation, the issue of applying a single algorithm of procedural actions of public administration bodies when sending materials of administrative-punishable cases to the court by filing an application with a requirement to bring to administrative responsibility, as already provided for in Chapter 25 of the Code of the Russian Federation on Administrative Offences, is proposed for discussion among scientists and legislators. And if it is necessary to transfer the materials of an administratively punishable case for consideration from one public administration body to another non-judicial body (public administration body), it is possible to provide for a ruling on the transfer of the case materials for consideration; 3) to regulate in the Code of the Russian Federation on Administrative Offences in the form of an independent chapter “Proceedings in administrative cases on the cancellation of a license and (or) permit” and provide for a single procedure for the review and resolution by the court of administrative cases of this category on administrative claims of public administration bodies.